Pelatihan Bekam (Al Hijamah) Sebagai Upaya Mewujudkan Kampung Sehat Pada Masa Pandemi Covid-19 di Desa Perengge Kabupaten Lombok Barat - Baiq Naili Dewi Atika; Dwi Kartika Risfianty; Irna Il Sanuriza; Khaerul Ihwan; Dara Puspita Anggraeni (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This community service activity aims to increase people's knowledge of how to do cupping properly and correctly, to create a healthy village during the pandemic, and as an effort to prevent the transmission of COVID-19 by promoting and preventive health measures. The method of implementing this service activity is by combining theories (discussion) 25% and practice 75%, as well as entrepreneurial provisions. There were 25 participants in the training. The evaluation instruments used were interviews, observation, and documentation. After all series of activities were carried out, the results of the service activity showed that the majority of participants had mastered the pre-cupping, cupping, and post-cupping procedures following the rules and procedures for the safety of the medical world.